2003
DOI: 10.3349/ymj.2003.44.6.987
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant / Antioxidant Status in Patients with Psoriasis

Abstract: Psoriasis is a common, chronic inflammatory skin disease with unknown etiology. Recently it has been suggested that increased ROS production and deficient function of antioxidant systems activities may be involved in the pathogenesis of the disease. Although there are several studies investigating oxidant/antioxidant systems in psoriatic patients, the data obtained from these studies is not concordant. In this study, superoxide dismutase (SOD) enzyme activity, and malondialdehyde (MDA) and antioxidant potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 0 publications
5
57
3
1
Order By: Relevance
“…Numerous studies found significantly decreased levels of serum Vitamin E [15][16][17] and erythrocyte catalase activity [18][19][20][21] in psoriasis patients. Whereas some research work did not found any significant change in the levels of antioxidants like serum vitamin E [16][17][18][19][20][21][22] and erythrocyte catalase activity [23] in psoriasis patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies found significantly decreased levels of serum Vitamin E [15][16][17] and erythrocyte catalase activity [18][19][20][21] in psoriasis patients. Whereas some research work did not found any significant change in the levels of antioxidants like serum vitamin E [16][17][18][19][20][21][22] and erythrocyte catalase activity [23] in psoriasis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some research work did not found any significant change in the levels of antioxidants like serum vitamin E [16][17][18][19][20][21][22] and erythrocyte catalase activity [23] in psoriasis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress and the increased formation of free radicals have been related to skin inflammation and are reported to be among the most important factors in the pathogenesis of psoriasis (Kiymat et al, 2003;Rocha et al, 2004;Relhan et al, 2002;Wolters, 2005). Studies demonstrate that individuals with psoriasis have high concentrations of malondialdehyde, OuvirLer foneticamentea marker of lipid peroxidation, and is compromised antioxidant status, with reduced levels of -carotene, -tocopherol and selenium (Azzini et al, 1995;Briganti & Picardo, 2003;Serwin et al, 2003).…”
Section: Oxidative Stress and Antioxidantsmentioning
confidence: 99%
“…25 Recently it has been suggested that increased reactive oxygen species (ROS) production and deficient function of antioxidant systems activities may be involved in the pathogenesis of the disease. 26 The carbonic anhydrase enzyme has recently been reported to have an anti-oxidant activity, which is glutathione- Original Article NJDVL -21 mediated. 27 Our earlier study demonstrated that the carbonic anhydrase activity had a strong correlation with lipid parameters.…”
Section: Introductionmentioning
confidence: 99%